Liquid Crystals: Nano‐Localized Heating Source for Photonics and Plasmonics (Advanced Optical Materials 12/2013). Issue 12 (December 2013) - De Sio, Luciano; Placido, Tiziana; Serak, Svetlana; Comparelli, Roberto; Tamborra, Michela; Tabiryan, Nelson; Curri, M. Lucia; Bartolino, Roberto; Umeton, Cesare; Bunning, Timothy
<x xml:space="preserve">Abstract</x> On page 899, conversion of near infrared radiation into heat, controlled at the nanoscale, is achieved by L. De Sio et al. and detected by exploiting the localized plasmonic resonance (LPR) of gold nanorods (GNRs) trapped in a nearly periodic Grandjean‐Cano texture of a thermotropic cholesteric liquid crystal (CLC). The localized heating from the nanosources induces a modification in the alignment of the surrounding CLC medium; this induces a variation of the CLC photonic bandgap and modifies the spectral position of the LPR of GNRs. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>